Clinical Pharmacology and Approach to Dose Selection of Emestedastat, a Novel Tissue Cortisol Synthesis Inhibitor for the Treatment of Central Nervous System Disease - Rolan, Paul; Seckl, Jonathan; Taylor, Jack; Harrison, John; Maruff, Paul; Woodward, Michael; Mills, Richard; Jaros, Mark; Hilt, Dana (Clinical pharmacology in drug development, 2025)
This review demonstrates the value of central pharmacodynamics (PD), including positron emission tomography (PET) and computerized cognitive testing, to supplement pharmacokinetic (PK) and peripheral PD for determining the target dose range for clinical efficacy testing of emestedastat, an 11β‐hydroxysteroid dehydrogenase 1 (11β‐HSD1) inhibitor. Combined data from 6 clinical trials in cognitively normal volunteers and patients with Alzheimer disease included a population PK model, endocrine PD, a human PET trial (11β‐HSD1 brain imaging), and computerized cognitive testing. PK and PET findings were similar in volunteers and patients with Alzheimer disease. PK modeling suggested that 20 mg daily would be optimal to maintain cerebrospinal fluid concentrations above the brain half maximal inhibitory concentration. However, subsequent PET scanning suggested that emestedastat doses of 10 or even 5 mg daily may be sufficient to adequately inhibit 11β‐HSD1. With once‐daily doses of 5‐20 mg in cognitively normal, older volunteers, a consistent pattern of pro‐cognitive benefit, without dose‐response, was seen as improvement in attention and working memory but not episodic memory. Thus, emestedastat therapeutic activity might be attained at doses lower than those predicted from cerebrospinal fluid drug levels. Doses as low as 5 mg daily may be efficacious and were studied in subsequent trials.